Predatory Encounters between Orb-Weaver Spiders of Genus Neoscona Simon, 1864 (Araneae: Araneidae) and some Odonates: a Case Study from Nauradehi Wildlife Sanctuary, Madhya Pradesh, India - Patil, Sachin R.; Chandra, Kailash; Bhandari, Rita; Talmale, S. S. (Indian Forester, 2016)
Prey and predator encounters are significant for studying predation behaviour of Orb-weaver spiders with reference to flying insects. Predatory encounters are studied between five species of Odonates (prey) and two species of Orb-weaver spiders (preadator) of Genus Neoscona belonging to family Araneidae based on four observations naturally occurred in the Nauradehi Wildlife Sanctuary, Madhya Pradesh, India during years 2012 and 2013 as different events. Factors involving behaviours of Orb-weaver spider and Odonate have influenced these predatory encounters.